Optimalisasi Manajemen Pendidik Dan Tenaga Kependidikan Di SMP N 20 Surabaya Untuk Meningkatkan Kualitas Pendidikan - Ayu Angela Rahma Hernowo; Siti Zakkiyah Hasya; Windasari Windasari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Optimizing the management of educators and education personnel has goals and strategies that can make SMPN 20 Surabaya a school with good management. Effective and competent strategies are the main key for educators and education staff so that the learning process can run well. Apart from that, performance evaluation is also necessary because it can make the work results of educators and education staff at SMPN 20 Surabaya more optimal in the future. The research method used is a qualitative approach. By using data collection techniques through interviews, observation and documentation so that it can support the success of this research. Optimizing the management of teaching and educational staff is indeed necessary, this is what can make a school a school that has a superior and competent vision, mission